DESAIN MESIN PEMARUT KELAPA DAN UBI KAYU DENGAN KOMBINASI ROL PARUT - Nanang Endriatno; Kadir Kadir (Jurusan Teknik Mesin, Universitas Halu Oleo, 2019)
This study aims to determine the safe shaft and to design a model of cassava and coconut grated machines. In this study, the grated machine was designed using Autodesk Inventor 2017. The material used for the shaft is carbon steel (S45C) with a tensile strength of 58 kg/mm2. The shaft calculation results show that the plan power is 4.0425 KW, torsional moment or torque at shaft speed 2670 rpm is 5124,955 kg.mm, and permissible shear stress is 4.83 (kg/mm2), and shaft diameter is 21 mm, while the shear stress is obtained at 2.823 kg/mm2. From the above results, it can be seen that the shear stress value that occurs is smaller than the permissible shear stress value (t<ta) where ta = 5,5 kg/mm and the value t = 2.823 kg/mm2, so it can be concluded that the shaft size planned safe. in this study, the design of the grated machine uses two different grated rollers for cassava and coconut. The pulp used is 4 pieces and grated rollers can be moved simultaneously or just one grated roller.